THE INFLUENCE OF LIFESTYLE ON THE CONSUMPTIVE BEHAVIOR OF KIP-K SCHOLARSHIP STUDENTS AT LP3I JAKARTA POLYTECHNIC - Anisa Prihatiningsih; Kiani Al Dina Putri; Riska Mubarokah (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Kartu Indonesia Pintar Kuliah (KIP-K) program aims to help high-achieving students from underprivileged families. However, lifestyle pressures in metropolitan cities like Central Jakarta and the Fear of Missing Out (FOMO) phenomenon trigger consumer behavior among students. This study aims to examine and analyze the influence of lifestyle on consumer behavior among KIP-K scholarship recipients at the LP3I Jakarta Polytechnic. The research method used is a quantitative descriptive research method. The population in this study were all KIP-K scholarship recipients at the LP3I Jakarta Polytechnic. Meanwhile, the sample used in this study was 50 students. Data collection was carried out by distributing questionnaires to KIP-K recipients at the LP3I Jakarta Polytechnic. The data analysis technique used in this study was linear regression analysis with the help of IBM SPSS software. Student lifestyle was measured using the AIO approach which includes the dimensions of activities, interests, and opinions. The results showed that lifestyle influences the consumer behavior of KIP-K scholarship recipients.